Factors affecting consumer purchase intention of halal ready-to-eat food products in Kelang Valley Malaysia - Suhaiza binti Safian (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
The aim of this research is to ascertain the factors that affect consumer purchase intention of halal ready-to-eat food products in Klang Valley, Malaysia. Demand for ready-to-eat food products due to its convenience has driven the growth of this industry. Ready-to-eat food products have become a lifestyle and a necessity for those residing in urban areas nowadays. However, the issues associated with ready-to-eat food products have become a stimulus to the demand for halal ready-to-eat food products due to rising concerns about health among the consumers. Primary data were collected through convenient sampling by distributing self-administered questionnaires to identify the factors affecting consumer purchase intention of halal ready-to-eat food products. A survey was conducted in Klang Valley, Malaysia, where data were collected from 300 respondents consisting of Muslim and non-Muslim consumers. Theory of planned behavior (TPB) was used as the conceptual framework, and the variables identified are attitude, subjective norms, perceived behaviour and one additional variable which is awareness. The collected data were tested by using multiple regression analysis in Statistical Package for the Social Sciences (SPSS). The findings show that all the variables are significant and can be accepted. Surprisingly, awareness was found to be the most significant factor that influences consumer purchase intention of halal ready-to-eat food products. This research is useful for marketing management and the policymakers, especially those involved in the halal ready-to-eat food industry. Researchers and academicians can benefit from the findings highlighted and can gain better insights into the purchase intention of consumers towards buying halal ready-to-eat food products.